Idiopathic inflammatory myopathy and non-coding RNA - Yang, Yang; GuangXuan, Hu; GenMeng, Wan; MengHuan, Li; Bo, Chang; XueJie, Yi (Frontiers in Immunology, 2023)
Idiopathic inflammatory myopathies (IIMs) are common autoimmune diseases that affect skeletal muscle quality and function. The lack of an early diagnosis and treatment can lead to irreversible muscle damage. Non-coding RNAs (ncRNAs) play an important role in inflammatory transfer, muscle regeneration, differentiation, and regulation of specific antibody levels and pain in IIMs.ncRNAs can be detected in blood and hair; therefore, ncRNAs detection has great potential for diagnosing, preventing, and treating IIMs in conjunction with other methods. However, the specific roles and mechanisms underlying the regulation of IIMs and their subtypes remain unclear. Here, we review the mechanisms by which micro RNAs and long non-coding RNA-messenger RNA networks regulate IIMs to provide a basis for ncRNAs use as diagnostic tools and therapeutic targets for IIMs.